Solution conformation of a deoxynucleotide containing tandem G.A mismatched base pairs and 3'-overhanging ends in d(GTGAACTT)2. - Lane, A; Martin, SR; Ebel, S; Brown, T (1992)
We have used 31P and 1H NMR spectroscopy and circular dichroism to define the solution conformation of d(GTGAACTT)2 which contains tandem G.A mismatched base pairs and 3'-overhanging TT ends. Measurements of coupling constants and NOE intensities show that the sugar puckers of the nucleotides are predominantly in the south domain (i.e., near C2'-endo) and that the glycosidic torsion angles are anti. The sequential NOE intensities indicate the presence of a right-handed helix. Analysis of the 31P and 1H NMR spectra of the duplex shows that the tandem mismatch forms a block in which there are unusual backbone torsion angles (i.e., in the BII state), within an otherwise B-like structure. The chemical shift of the N1H of the mismatched guanosine and NOEs between the mismatched base pairs and their nearest neighbors are inconsistent with the imino pairing present in single A.G mismatches or in the X-ray structure of a tandem mismatch [Privé, G. G., et al. (1987) Science 238, 498-503] but the data are consistent with the amino pairing found by Li et al. (1991) [Li, Y., et al. (1991) Proc. Natl. Acad. Sci. U.S.A. 88, 26-30]. The strong base-base stacking both within the tandem G.A block and between the G.A mismatches and their other nearest neighbors offsets the intrinsic destabilizing effects of the mismatch. Further, the 3'-TT overhangs stack onto the ends of the helix and stabilize the duplex against fraying, which accounts for the observed increase in the melting temperature compared with the flush-ended duplex.